Habitat amount is a driver for biodiversity, but not for the carbon stock in post-logging natural regenerating areas in Tropical Atlantic Forest. (September 2022) - Capellesso, Elivane Salete; da Rosa, Carolina Machado; Magnago, Luiz Fernando Silva; Marques, Renato; Marques, Marcia C.M.
Abstract: Natural regeneration has been considered an important strategy for improving large-scale forest restoration to revert the losses resulting from the fragmentation of tropical landscapes in recent years. However, local, regional, and spatial factors can influence the dynamics of regeneration, thereby affecting its efficiency. We investigated how time after disturbance, landscape characteristics, and climate gradients affect the efficiency of natural regeneration in the Brazilian Atlantic Forest. We searched for studies that addressed the post-logging regenerating of forests throughout the biome. For each included study, we extracted the forest age, species richness, and basal area (used as an estimate of carbon). Additionally, for each studied site (total 100 sites) we used land use maps to extract the landscape metrics and obtained bioclimatic variables from the global dataset. Further, we used forest age, landscape metrics, and bioclimatic variables to build models and predict forest species richness and carbon stock. Our results showed that species richness was positively affected by habitat amount (evaluated through patch area and perimeter-area ratio), isothermality, and forest age. Carbon stock was positively affected only by the forest age. These findings show that natural regeneration will yield the best results in terms of conserving the biodiversity among landscapes with a large number of habitats. Conversely, a landscape with a predominance of mature forest will be more efficient as carbon stock. We conclude that, when planning the restoration of large-scale landscapes, natural regeneration must be considered along with other strategies to ensure that multiple objectives are achieved. Highlights: Greater amount of habitat positively affects the species richness. Isothermally is an important variable for species richness. The forest age affects the carbon stock. Natural regeneration is efficient to recover the diversity and carbon stock.